Non-natural Amino Acid Fluorophores for One- and Two-Step FRET Applications(†) - Rogers, Julie M. G. (2009)
Fluorescence resonance energy transfer (FRET) provides a powerful means to study protein conformational changes. However, the incorporation of an exogenous FRET pair into a protein could lead to undesirable structural perturbations of the native fold. One of the viable strategies to minimizing such perturbations is to use non-natural amino acid based FRET pairs. Previously we have shown that p-cyanophenylalanine (Phe(CN)) and tryptophan (Trp) constitute such a FRET pair, useful for monitoring protein folding-unfolding transitions. Herein, we further show that 7-azatryptophan (7AW) and 5-hydroxytryptophan (5HW) can also serve as a FRET acceptor to Phe(CN), and the resultant FRET pairs offer certain advantages over Phe(CN)-Trp. For example, the fluorescence spectrum of 7AW is sufficiently separated from that of Phe(CN), making it straightforward to decompose the FRET spectrum into donor and acceptor contributions. Moreover, we show that Phe(CN), Trp and 7AW can be used together to form a multi-FRET system, allowing more structural information to be extracted from a single FRET experiment. The applicability of these FRET systems is demonstrated in a series of studies wherein they are employed to monitor the urea-induced unfolding transitions of the villin headpiece subdomain (HP35), a designed ββα motif (BBA5), and the human Pin1 WW domain.